Alcohol Consumption in Patients with Non‐alcoholic Fatty Liver Disease: Convenient vs. Inconvenient Truths. (October 2018) - Armstrong, Matthew J.; Mellinger, Jessica L.; Trivedi, Palak J.
Abstract: : N/A: Understanding the role of modest alcohol consumption in patients with non‐alcohol induced fatty liver disease (NAFLD) remains a significant challenge, with no clear guidance on counselling regarding alcohol use. Conventionally, the strong association of alcohol excess and development of complications related to chronic liver disease, including hepatocellular carcinoma, has led practitioners to advocate complete abstinence to those with NAFLD. New evidence published in this issue of the Red Journal challenges the historic paradigm by showing that modest, non‐binge wine consumption (<70 g/week) associates with significantly lower risk of advanced hepatic fibrosis on biopsy compared with complete abstinence across a well‐characterised single centre cohort of nearly 200 patients with NAFLD.